PENGARUH TEKANAN KETAATAN, KOMPLEKSITAS TUGAS, DAN PENGALAMAN AUDITOR TERHADAP AUDIT JUDGMENT: STUDI KASUS PADA KANTOR AKUNTAN PUBLIK DI BALI - Henry Rievaldy; I Gusti Agung Krisna Lestari (Journal Research of Accounting, 2021)
The formulation of the problem and the objectives of this study were to determine the effect of compliance pressure, task complexity and auditor experience on audit considerations. The location of this research is the Public Accounting Firm in Bali. The population uses auditors at the Public Accounting Firm in Bali and the sample used is 61 respondents. The data analysis technique used is Validity, Reliability, Classical Assumptions, Multiple Linear Regression, Coefficient of Determination, t-test and F-test. regression 0.338, and sig 0.001. (2) complexity has a significant negative effect on audit judgment, where the regression coefficient value is - 0.476, and sig 0.000. (3) auditor experience has a significant positive effect on audit judgment, where the regression coefficient is 0.192, and sig is 0.021. The magnitude of the influence of the independent variables on audit judgment is 53.8%. The suggestion in this study is that Public Accounting Firms in Bali are expected to always supervise auditors in conducting audits, always provide audit assignments that are in accordance with the auditor's abilities and routinely perform audit rotations.